Foreign language acquisition and argumentative activity - Musialek, Danièle (Íkala, Revista de Lenguaje y Cultura, 1996)
I will first characterize the participatory framework of an interactional story, and then report on the argumentative activity constructed in the French lect of a Polish speaker. This interaction involves three participants: the informant Misia (Ma), her sister Marzena (Mz) and the investigator (Da). The meeting was arranged in Marzena's apartment.